An improved procedure for the synthesis of fluoromethylketones: Flash vacuum pyrolytic elimination - Vichai Reutrakul (2018)
Fluoromethylketones 3 are synthesized in good yields by a flash vacuum pyrolytic elimination of 2. Studies on the improved synthesis of 2 leads to the evidence on the existence of α,α-dilithio fluoromethyl phenyl sulfoxide. © 1994.